THE TIMELESSNESS OF MAXIMAL MUSIC - Menezes, Flo [UNESP] (My University, 2011)
If we consider as music that speculative, pleasant activity, yes, but which is at the same time essentially investigative, experimental in nature – the radicalism of which standing above all on the dialectical relationship between the new and the revisitation of the old in a new context –, we should recognize that, since such field of knowledge exists in a considerably autonomous manner, it has always been connected to its close cousins: mathematics and physics. From the earliest times, when Pythagoras expressed his view concerning the harmony of spheres, passing through the trivium and quadrivium of the Middle Ages and later through the scientific further developments of that Pythagorean concept by Johannes Kepler [2], until contemporaneity, when physicists themselves appeal to musical constitutions to solve problems of physics and the universe, the degree of relativeness between music and science is remarkable and evident. Simultaneities, decompositions, space/time and light are discussed here under an aesthetic approach.
Keywords: Decomposition space; Further development; Middle ages; Pythagoras; Revisitation; Spacetime